THE EFFECT OF COMPENSATION SCHEMES, OBEDIENCE PRESSURE, AND SELF-EFFICACY ON BUDGETARY SLACK - Dimietry Anastasia; Lodovicus Lasdi (Journal of Applied Finance & Accounting, 2022)
Budgetary Slack is the most common problem when preparing a budget. Budgetary Slack occurs when there is a difference between the number of best budget estimates and the total budget proposed by subordinates. Several factors can affect budgetary slack, including compensation schemes, obedience pressure, and self-efficacy. This experimental study examines and analyzes the effect of compensation schemes, obedience pressure, and self-efficacy on budgetary slack. This experiment used a 2x2x2 between-subject experimental design; participant data was obtained by filling out a google form. Testing of participant data was used using Levene's test and univariate ANOVA. The conclusion is that budgetary slack is affected by the compensation scheme. Therefore, managers should be aware of the benefits and drawbacks of the pay plan that the firm will implement in advance.